Initiatives and Challenges of The Kampus Mengajar Program to Pursue Freedom to Learn - Sri Lestari; Khusnul Fatonahr; Abdul Halim; Lintang Marselesa Aurra; Selindah Rahmawati (Pedagonal : Jurnal Ilmiah Pendidikan, 2022)
This study is aimed at exploring the implementation of Kampus Mengajar to pursue the freedom to learn. Kampus Mengajar is a national program as a part of the Merdeka Belajar Kampus Merdeka (MBKM) policy by the Ministry of Education and Culture of Indonesia. This program is to help schools solve their problems and make improvements in the disruptive era, especially during the COVID-19 outbreak by sending university students to targeted schools all over Indonesia. The research involved the participants of the Kampus Mengajar program in a private elementary school in Jakarta. Data were obtained from the interview and document analysis to find out the initiatives and the challenges of conducting the program. The data were analyzed qualitatively. The findings show that to help schools, the participants planned various initiatives during the program. The main challenges of implementing the initiatives include teachers’ passive participation and lack of school facilities. It can be concluded that the Kampus Mengajar program contributes to pursuing the freedom to learn at school. However, to overcome the problems and make continuous improvements, it is not enough to count on the participants of the Kampus Mengajar program. It needs the school principal's full support and teachers’ commitment to making changes.